Education and Early Screening: Efforts to Control Diabetes Mellitus at Pampang Community Health Center, Makassar City - Syaipuddin, Syaipuddin; Suhartatik, Suhartatik; Haskas, Yasir; Nurbaya, Sitti (International Journal of Public Devotion, 2025)
ABSTRACTIn Indonesia, including in Makassar City, the prevalence of diabetes mellitus (DM) continues to increase. To control diabetes mellitus (DM), an integrated approach must be implemented, which includes health education and early screening. The purpose of this community service program is to increase public awareness about diabetes mellitus, the importance of a healthy lifestyle, and identify individuals who are at risk of diabetes mellitus in the work area of the Pampang Health Center. Health counseling, blood sugar checks, and training on healthy food and exercise are all part of the program.The methods used in this program include interactive lectures, group discussions, and individual health screenings. The target audience of the program is the vulnerable population, including individuals with a family history of DM and those with a sedentary lifestyle. The results show an increase in participants' understanding of DM risk factors and prevention measures. In addition, blood glucose testing helps identify individuals who need further referral for diagnosis and treatment. This program has a positive impact on raising community awareness of the importance of early detection and DM control through behavioral changes. It is expected that this activity can continue and become a model for community-based DM control in other regions. Collaboration between educational institutions, healthcare professionals, and the community is key to the success of this program in reducing the incidence of DM at Pampang Community Health Center, Makassar City.Edukasi dan Pemeriksaan Dini: Upaya Pengendalian Diabetes Mellitus di Puskesmas Pampang Kota MakassarABSTRAKDi Indonesia, termasuk di Kota Makassar, prevalensi diabetes mellitus (DM) terus meningkat. Untuk mengendalikan diabetes mellitus (DM), pendekatan terpadu harus diterapkan, yang mencakup pendidikan kesehatan dan pemeriksaan dini. Tujuan dari program pengabdian masyarakat ini adalah untuk meningkatkan kesadaran masyarakat tentang diabetes melitus, pentingnya pola hidup sehat, dan mengidentifikasi individu yang berada di bawah risiko diabetes melitus di wilayah kerja Puskesmas Pampang. Penyuluhan kesehatan, pemeriksaan gula darah, dan pelatihan tentang makanan dan olahraga yang sehat adalah semua bagian dari program ini. Program ini menggunakan ceramah interaktif, diskusi kelompok, dan pemeriksaan kesehatan individu. Program ini bertujuan untuk masyarakat yang rentan, seperti orang yang memiliki riwayat DM dalam keluarga mereka dan orang yang kurang aktif dalam gaya hidup mereka. Hasil acara menunjukkan bahwa peserta lebih memahami faktor risiko DM dan cara mencegahnya. Pemeriksaan gula darah juga membantu menemukan orang yang memerlukan rujukan lanjutan untuk diagnosis dan perawatan lebih lanjut.   Program ini meningkatkan kesadaran masyarakat akan pentingnya deteksi dini DM dan pengendaliannya melalui perubahan perilaku. Diharapkan program ini akan berlanjut dan menjadi model pengendalian DM berbasis komunitas di wilayah lain. Sukses program ini dalam menekan angka DM di Puskesmas Pampang, Kota Makassar, bergantung pada kolaborasi antara institusi pendidikan, tenaga kesehatan, dan masyarakatKata Kunci :Diabetes Mellitus; Edukasi Kesehatan; Pemeriksaan Dini; Pengendalian Diabetes